Plasticity in colonization and mycorrhizal benefit in the common Arctic species Avenella flexuosa in response to grazing ... - Kytöviita, Minna-Maarit; Francini, Gaia (Taylor & Francis, 2025)
Arctic grasslands are intensively grazed. The common grass Avenella flexuosa is particularly common in grazed areas, but the mechanisms of its adaptation to grazing are not fully known. We tested whether the plasticity of arbuscular mycorrhizal symbiosis in Avenella flexuosa roots contributes to its adaptation to grazing. We observed a clear decline in arbuscular mycorrhizal symbiont root colonization in Avenella flexuosa as a response to grazing in arctic meadow ecosystems in Northern Fennoscandia. In the greenhouse, arbuscular mycorrhizal fungi and fine endophytes responded negatively to fertilization, while the effect of removing foliage was marginally significant. These results indicate that the negative effect of reindeer grazing on arbuscular mycorrhizal frequency in Avenella flexuosa in field are mechanistically caused by increased nitrogen availability rather than consumption of foliage. The benefit of the symbiosis was positive for both plant and the fungus in the greenhouse as indicated by ...